2015
DOI: 10.1037/spq0000082
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the change in latent statuses in bullying behaviors across time.

Abstract: Involvement in bullying and victimization has been mostly studied using cross-sectional data from 1 time point. As such, much of our understanding of bullying and victimization has not captured the dynamic experiences of youth over time. To examine the change of latent statuses in bullying and victimization, we applied latent transition analysis examining self-reported bullying involvement from 1,180 students in 5th through 9th grades across 3 time points. We identified unobserved heterogeneous subgroups (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 56 publications
(96 reference statements)
3
45
1
1
Order By: Relevance
“…To date, little is known about the extent to which the bullying roles are stable or fluid over time (Gumpel et al, 2014;Ryoo, Wang, & Swearer, 2015). There is some emerging evidence that the majority of youth who report involvement have infrequent experiences (Ryoo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, little is known about the extent to which the bullying roles are stable or fluid over time (Gumpel et al, 2014;Ryoo, Wang, & Swearer, 2015). There is some emerging evidence that the majority of youth who report involvement have infrequent experiences (Ryoo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as an individual, you may find yourself in various social situations related to bullying: you may be an observer (by-stander), you may be undergoing aggression (victim), or you may be the one perpetuating this behavior (bully) [35].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Similarly, Ryoo, Wang, and Swearer (2014) found instability in being a victim or bully over time, particularly during school transition years. Likewise, a combined cohort study by Baly, Cornell and Lovegrove (2014) found a high degree of variance in selfand peer-reports of bullying other students across six waves of surveys across three years, and that the majority of the reported bullying was transient.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Rosen et al, (2009), in a longitudinal study of 'social victimization' , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 reported that children victimized at one developmental period were not necessarily 'chronically' victimized at a later point in time. Later research by Nocentini, Menesini, and Salmivalli (2013), using multi-level growth models, showed that bullying experiences varied significantly across time at both the individual and classroom levels.Similarly, Ryoo, Wang, and Swearer (2014) found instability in being a victim or bully over time, particularly during school transition years. Likewise, a combined cohort study by Baly, Cornell and Lovegrove (2014) found a high degree of variance in selfand peer-reports of bullying other students across six waves of surveys across three years, and that the majority of the reported bullying was transient.…”
mentioning
confidence: 99%